Epistemología y didáctica del proceso de enseñanza-aprendizaje en arquitectura y diseño industrial - Mosquera Téllez, Jemay (Universidad de San Buenaventura - Cali, 2017)
This paper aims to meet the demands of the contemporary world on local development processes, training of human resources and competitiveness. In particular, it intends to make epistemological and academic contributions to competence training in architecture and industrial design, by describing disciplinary changes and contradictions, the analysis of the teaching-learning process, and the practice of knowledge on pedagogy and didactics, in order to propose a logical and flexible sequence in this process that is directly related to the development of skills, and maximize the theoretical and practical basis for the development of competent students with an optimal social and professional performance.